57.2k views
3 votes

\begin{gathered}f(x) = (5)/(x - 4) \: \: \: g(x) (6)/(x) \: \: \: \\\end{gathered}find f°g(x).

\begin{gathered}f(x) = (5)/(x - 4) \: \: \: g(x) (6)/(x) \: \: \: \\\end{gathered-example-1

1 Answer

2 votes

Given


f(x)=(5)/(x-4),\text{ }g(x)=(6)/(x)

To find:


f\circ g(x)

Step-by-step explanation:

It is given that,


f(x)=(5)/(x-4),\text{ }g(x)=(6)/(x)

That implies,


\begin{gathered} f\circ g(x)=f(g(x)) \\ =f((6)/(x)) \\ =(5)/((6)/(x)-4) \\ =(5)/((6-4x)/(x)) \\ =(5x)/(6-4x) \\ =(5x)/(2(3-2x)) \end{gathered}

Hence, the value is,


f\circ g(x)=(5x)/(2(3-2x))

And, the domain is,


\begin{gathered} 6-4x=0 \\ 4x=6 \\ x=(6)/(4) \\ x=(3)/(2) \end{gathered}

Therefore, the domain is,


Domain:(-\infty,(3)/(2))\cup((3)/(2),\infty)

User Blotto
by
4.6k points